Passion Complex : selected works from the Albright-Knox Art Gallery - 21st Century Museum of Contemporary Art, Kanazawa (Kanazawa : 21st Century Museum of Contemporary Art Kanazawa, 2007)
Arcangel, Cory ; Balkenhol, Stephan ; Batchelor, David ; Bourgeois, Louise ; Calle, Sophie ; Coplans, John ; Coyne, Petah ; Riverhead (New York) ; Hammons, David ; Hatoum, Mona ; Lambie, Jim ; Opie, Catherine ; Simmons, Laurie ; Wall, Jeff ; Wearing, Gillian
biog. per kunstenaar
Engels, Japans
Exhibition. Passion Complex : Selected Works from the Albright-Knox Art Gallery. Kanazawa. 21st Century Museum of Contemporary Art Kanazawa. 2007-08-01. 2007-11-11
boek